Perubahan Visual Karakter The Sims 2 ke The Sims 3 dan Interaksi Pemain - Ratna Ratna; Iman Sudjudi (Wimba : Jurnal Komunikasi Visual, 2010)
Character is an essential element in a game, which connects players with the world of game. As an instrument, visual Character plays a major role in eliciting the excitements from the player as user. Today many game characters changed into becoming more humanlike, one of them is a character from The Sims 2 to The Sims 3.Research was conducted to discover whether visual character transformation from The Sims 2 to The Sims 3 gives off more emotion of enjoyment to characters and creates an interaction between player and character that is entertaining. To achieve this, quantifiable quantitative methods were used to learn a player's perception about visual character transformation between the two games. Upon ascertaining the player's perception, emotion elicited from the transformation and discrepancies in interaction were also examined.The results showed that TS3 has a distinctive character more dynamic and emotional in talking behavior, but omit the features of the content of conversations and background characters. Perception of respondents on the basis of this assessment that they prefer TS3 polished character of his attitude. This polishment adds visual strength of character associated with the emergence of identity, character, behavior of speech, emotion and dynamism role. TS3 visual character of the more interesting it makes the interaction between respondents with TS3 lasted more pleasant character.